Normal aging and decision-making: a systematic review of the literature of the last 10 years - Carine Carolina Wiesiolek; Maria Paula Foss; Paula Rejane Beserra Diniz (Jornal Brasileiro de Psiquiatria, 2014)
Objective Conduct a systematic review to investigate whether healthy elderly have deficits in the decision-making process when compared to the young. Methods We performed a systematic search on SciELO, Lilacs, PsycINFO, Scopus and PubMed database with keywords decision making and aging (according to the description of Mesh terms) at least 10 years. Results We found nine studies from different countries, who investigated 441 young and 377 elderly. All studies used the IOWA Gambling Task as a way of benchmarking the process of decision making. The analysis showed that 78% of the articles did not have significant differences between groups. However, 100% of the studies that assessed learning did find relevant differences. Furthermore, studies that observed the behavior of individuals in the face of losses and gains, 60% of articles showed that the elderly has more disadvantageous choices throughout the task. Conclusion: The consulted literature showed no consensus on the existence of differences in performance of the decision-making process between old and young, but it is observed that the elderly has deficits in learning and a tendency to fewer advantageous choices.